Humanized NOD/SCID/IL2rγnull mice exhibit functionally augmented human regulatory T cells associated with enzymatic up‐regulation of H3K27me3 in comparison with humans. (4th March 2021) - Takahashi, H.; Tsuboi, H.; Abe, S.; Honda, F.; Kondo, Y.; Matsumoto, I.; Sumida, T.
Summary: Humanized non‐obese diabetic/severe combined immunodeficiency/interleukin‐2 receptor‐γ‐null (NOD/SCID/IL2rγ null ) [humanized (huNSG)] mice engrafted with human hematopoietic cells have been used for investigations of the human immune system. However, the epigenetic features of the human regulatory T (Treg ) cells of huNSG mice have not been studied. The objective of this study was to clarify the characteristics of human Treg cells in huNSG mice, especially in terms of the epigenetic aspects. We compared the populations, inhibitory molecule expression and suppressive capacity of human Treg cells in spleens harvested from the huNSG mice 120 days after the engraftment of human umbilical cord blood CD34 + cells with human peripheral blood mononuclear cells (PBMCs). Histone modifications and enhancer of zeste homolog 2 (Ezh2), an H3K27 methyltransferase, of human Treg cells were quantified in huNSG mice and human PBMCs. The effect of Ezh2 inhibitor on human Treg cells exposed to interleukin (IL)‐6 was also compared between them. Human Treg cells in the spleens of huNSG mice showed an increased proportion among CD4 + T cells, higher expressions of forkhead box protein 3 (FoxP3), cytotoxic T lymphocyte antigen 4 (CTLA‐4) and glucocorticoid‐induced tumor necrosis factor‐related protein (GITR), a higher production of IL‐10 and enhanced suppressive capacity when compared with those in human PBMCs. H3K27me3 and Ezh2 were specifically up‐regulated in human Treg cells of huNSG mice in comparison with those of human PBMCs. The decrease in Treg cells induced by IL‐6 exposure was attenuated in huNSG mice when compared with human PBMCs, while the difference between them was cancelled by addition of Ezh2 inhibitor. In conclusion, huNSG mice exhibit functionally augmented human Treg cells owing to enzymatic up‐regulation of H3K27me3. Abstract : Humanized NOD/SCID/IL2rγnull (huNSG) mice engrafted with human hematopoietic cells exhibited functionally augmented human Treg cells. The higher Treg cell stability in huNSG mice depended on enhanced enhancer of zeste homolog 2 (Ezh2)‐mediated trimethylated histone H3 at lysine 27 (H3K27me3) modification in Treg cells. This is the first report to show the epigenetic features of human Treg cells in huNSG mice.